Synthesis, characterization and photophysical properties of Eu3+ doped in BaMoO4 - Rosa, Ieda L. V.; Marques, Ana Paula A.; Tanaka, Marcos T. S.; Melo, Dulce M. A.; Leite, Edson R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Springer/plenum Publishers, 2008)
In this work Ba0.99Eu0.01MoO4 (BEMO) powders were prepared by the first time by the Complex Polymerization Method. The structural and optical properties of the BEMO powders were characterized by Fourier Transform Infra-Red (FTIR), X-ray Diffraction (XRD), Raman Spectra, High-Resolution Scanning Electron Microscopy (HR-SEM) and Photoluminescent Measurements. XRD show a crystalline scheelite-type phase after the heat treatment at temperatures greater than 400 degrees C. The ionic radius of Eu3+ (0.109 nm) is lower than the Ba2+ (0.149 nm) one. This difference is responsible for the decrease in the lattice parameters of the BEMO compared to the pure BaMoO4 matrix. This little difference in the lattice parameters show that Eu3+ is expected to occupy the Ba2+ site at different temperatures, stayed the tetragonal (S-4) symmetry characteristic of scheelite-type crystalline structures of BaMoO4. The emission spectra of the samples, when excited at 394 nm, presented the D-5(1)-> F-7(0, 1 and 2) and D-5(0)-> F-7(0, 1, 2, 3 and 4) Eu3+ transitions at 523, 533, 554, 578, 589, 614, 652 and 699 nm, respectively. The emission spectra of the powders heat-treated at 800 and 900 degrees C showed a marked increase in its intensities compared to the materials heat-treated from 400 to 700 C. The decay times for the sample were evaluated and all of them presented the average value of 0.61 ms. Eu3+ luminescence decay time follows one exponential curve indicating the presence of only one type of Eu3+ symmetry site.
Keywords: europium; molybdate; Complex Polymerization Method; photoluminescence